To solve the equation \(-2.4x - 1.1 = 3.7\), we'll perform the steps as follows:
-
Add 1.1 to both sides:
\(-2.4x - 1.1 + 1.1 = 3.7 + 1.1\)
This simplifies to:
\(-2.4x = 3.7 + 1.1\)
Now calculate \(3.7 + 1.1\):
\(3.7 + 1.1 = 4.8\)
So we have:
\(-2.4x = 4.8\)
-
Divide both sides by -2.4:
\(x = \frac{4.8}{-2.4}\)
Now calculate \(\frac{4.8}{-2.4}\):
\(4.8 \div -2.4 = -2.0\)
So, the completed solution is:
- For \(-2.4x = \), the answer is \(4.8\).
- For \(x = \), the answer is \(-2.0\).
Final answer:
- \(-2.4x = 4.8\)
- \(x = -2.0\)